2023
DOI: 10.1101/2023.02.28.530406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic characterization ofUstilago maydissirtuins shows Sir2 as a modulator of pathogenic gene expression

Abstract: Phytopathogenic fungi must adapt to the different environmental conditions found during infection and avoid the immune response of the plant. For these adaptations, fungi must tightly control gene expression, allowing sequential changes in transcriptional programs. In addition to transcription factors, chromatin modification is used by eukaryotic cells as a different layer of transcriptional control. Specifically, the acetylation of histones is one of the chromatin modifications with a strong impact on gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 84 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…In plant fungi, several Sir2 family deacetylases have been characterized, which distributed in nuclei and functioned as modulators of pathogenic gene expression (Fernandez et al ., 2014; Cai et al ., 2021; Navarrete et al ., 2023). Our previous study showed that the Fol sirtuin FolSir2 predominantly resides in the cytoplasm (Zhang et al ., 2023), which is different from the rest of these proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In plant fungi, several Sir2 family deacetylases have been characterized, which distributed in nuclei and functioned as modulators of pathogenic gene expression (Fernandez et al ., 2014; Cai et al ., 2021; Navarrete et al ., 2023). Our previous study showed that the Fol sirtuin FolSir2 predominantly resides in the cytoplasm (Zhang et al ., 2023), which is different from the rest of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…B. Li et al ., 2020), the complicated interactions among the multiple substrates may contribute to the unaffected phenotype in mycelial growth of FolSir2 knockout mutants. Similar results can be observed in U. maydis and M. oryzae , in which loss of UmSir2 and MoSir2 function in Δsir2 strains did not affect fungal growth, but attenuated the virulence (Fernandez et al ., 2014; Navarrete et al ., 2023). Moreover, FolSir2 homologues with similar functions are also present in B. cinerea and other phytopathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these fungi, deletion of genes encoding HAT family members affected fungal virulence as well as lifestyle switches [60][61][62]. In U. maydis, activity of the HDAC member Sir2 is involved in pathogenic development, although it is unclear whether Sir2 is truly active in deacetylation [63]. Recent results in Saccharomyces cerevisiae have raised concerns about the role of histone acetylation in transcriptional regulation, as temporal experiments show that transcriptional activation occurs before histone acetylation, which suggests that even though histone acetylation may be involved in transcriptional regulation during disease development, it may not directly activate transcription [64].…”
Section: Epigenetic Mechanisms Affect Transcriptionmentioning
confidence: 99%